Detection of atypical porcine pestivirus genome in newborn piglets affected by congenital tremor and high preweaning mortality1. (9th August 2019) - Sutton, Kylee M; Lahmers, Kevin K; Harris, Seth P; Wijesena, Hiruni R; Mote, Benny E; Kachman, Stephen D; Borza, Tudor; Ciobanu, Daniel C
Abstract: Recently, piglets from a high-health status farm began exhibiting congenital tremors, high preweaning mortality and incidence of splayed legs. Postmortem histological examination identified a small number of scattered white matter vacuoles in the cerebellum and underlying brainstem of affected piglets. Presence of potential viral sources associated with this neurologic condition was initially infirmed using quantitative PCR for atypical porcine pestivirus (APPV ), porcine teschovirus, and porcine sapelovirus. Using metagenomic analysis, APPV was identified as the main microbial species in serum obtained from piglets affected by congenital tremor. These piglets had higher preweaning mortality rates (46.4% vs. 15.3%) and incidence of splayed legs (33.0% vs. 0.8 %) compared to unaffected piglets. Piglets affected by congenital tremor had higher viral titer ( P < 0.15) and larger birth weights ( P < 0.05) compared to normal litter mates. Whole-genome sequencing and genome assembly of the novel APPV strain (MK728876) was carried out using Oxford Nanopore and related bioinformatics pipelines. Phylogenic analysis demonstrated that this strain along with other completely sequenced APPV strains were grouped into 2 clades, both including strains-inducing congenital tremor. Strains appear to cluster based on region but there were still significant differences within regions. Future research needs to address potential underdiagnosis due to genetic diversity but also to understand mode of transmission, variation in virulence, and the role of host genetics in APPV susceptibility.